Preliminary Evaluation of Matrix Metalloproteinase-13 Selective Radiotracers for Imaging Atherosclerosis - Al Haddad, Rami (Université d'Ottawa / University of Ottawa, 2020)
Introduction: Rupture of atherosclerotic plaques is associated with strokes, myocardial infarctions and cardiovascular complications. Collagen, known to be the most abundant protein in atherosclerotic plaques, stabilizes the cap and prevents the lesion from rupture. One of the enzymes responsible for cleaving collagen in plaques is MMP-13. Therefore, we hypothesized that imaging MMP-13 in atherosclerotic plaques using PET radiotracers can be a good indicator in monitoring plaque development and stability. Results: Our results indicate that developing potent selective MMP-13 inhibitors is possible and radiolabeling these compounds, although challenging, can be a useful tool for imaging MMP-13 in atherosclerotic plaques. Autoradiography and staining techniques show colocalization of our tracer with lipids, an essential indicator of the presence of atherosclerotic lesions. In addition, it was shown that the tracer had similar uptake in both groups of mice, confirmed by PET and biodistribution data. However, more selective MMP-13 tracers need to go though this process. Furthermore, more exclusive atherosclerotic markers should be stained for to confirm that the tracer is most selective for MMP-13. Conclusion: In conclusion, this study was useful in identifying MMP-13 inhibitors with radiolabeling potential to image MMP-13 in atherosclerotic plaques.
Keywords: MMP-13; Atherosclerosis; Cardiovascular diseases; Positron Emission Tomography; PET; Autoradiography; Imaging; Tracer; Enzyme assay; Biodistribiution; Autoradiography